Catalysis derived from flower-like Ni MOF towards the hydrogen storage performance of magnesium hydride. (19th February 2022) - Gao, Haiguang; Shi, Rui; Shao, Yuting; Liu, Yana; Zhu, Yunfeng; Zhang, Jiguang; Li, Liquan
Abstract: Herein, a novel flower-like Ni MOF with good thermostability is introduced into MgH2 for the first time, and which demonstrates excellent catalytic activity on improving hydrogen storage performance of MgH2 . The peak dehydrogenation temperature of MgH2 -5 wt.% Ni MOF is 78 °C lower than that of pure MgH2 . Besides, MgH2 -5 wt.% Ni MOF shows faster de/hydrogenation kinetics, releasing 6.4 wt% hydrogen at 300 °C within 600 s and restoring about 5.7 wt% hydrogen at 150 °C after dehydrogenation. The apparent activation energy for de/hydrogenation reactions are calculated to be 107.8 and 42.8 kJ/mol H2 respectively, which are much lower than that of MgH2 doped with other MOFs. In addition, the catalytic mechanism of flower-like Ni MOF is investigated in depth, through XRD, XPS and TEM methods. The high catalytic activity of flower-like Ni MOF can be attributed to the combining effect of in-situ generated Mg2 Ni/Mg2 NiH4, MgO nanoparticles, amorphous C and remaining layered Ni MOF. This research extends the knowledge of elaborating efficient catalysts via MOFs in hydrogen storage materials. Graphical abstract: Image 1 Highlights: A novel flower-like Ni MOF with good thermostability is fabricated. Flower-like Ni MOF can effectively improve the hydrogen storage property of MgH2 . MgH2 -5 wt.% Ni MOF can release 6.4 wt.% H2 at 300 °C within 600 s. Partial MOF reacts with MgH2 to form Mg2 Ni/Mg2 NiH4, MgO nanoparticles, amorphous C. The combining effect of in-situ formed substances and residual Ni MOF is revealed.